Pemberdayaan Masyarakat dalam Usaha Penguatan Literasi dan Numerasi: Studi di Desa Putat Kidul Kecamatan Gondanglegi Kabupaten Malang - Syahrani, Regita Pinkan; Kriswibowo, Arimurti (VISA: Journal of Vision and Ideas, 2024)
The implementation of Community Empowerment is an important process in improving the quality of life of the community and increasing community participation. One of them is in strengthening literacy, which is a key strategy in increasing the capacity of individuals and community groups to face challenges in an increasingly complex information age. This study aims to explain the concepts, strategies, and impacts of community empowerment implementation by explaining how community empowerment is implemented in various contexts of strengthening literacy, focusing on improving the ability to read, write, and understand information in Putat Kidul Village. The research method used in this journal is a qualitative research method by conducting interviews, observations, and document analysis to collect data with community members involved in empowerment programs. The author uses 4 research focuses, namely the provision of resources, opportunities, knowledge and skills. The results of this study show that community empowerment in an effort to strengthen literacy and numeracy in Putat Kidul Village, Gondanglegi District has not been carried out optimally due to inadequate technological resources for the teaching and learning process such as laptops and projectors.